Emplacement of the 2.44 Ga ultramafic layered Kemi intrusion, Finland PGE, geochemical and Sm-Nd isotopic implications - Linkermann, Sean Aaron (Rhodes University, Faculty of Science, Department of Geology, 2011)
Europe's largest chrome deposit is hosted by the 2.44 Ga Kemi ultramafic layered intrusion. The lower half of the intrusion consists of peridotites, pyroxenites and chromitite layers while the upper half consists of websterites, gabbronorites and leucogabbros. The mafic minerals of the lower and upper parts of the intrusion are altered to serpentine, chlorite, talc, amphiboles and carbonates. However, the original mineralogy is still preserved in the middle part of the intrusion. Earlier work on the Kemi intrusion concentrated mainly on the economically important chromitite layers and suggested that these layers were formed through contamination of a single pulse of primitive magma by underlying Archaean basement crustal material. The broad variations of the major element concentrations reflect variations in the mode of the Kemi rocks. The petrology, which shows olivine- and orthopyroxene-dominated rocks in the lower portion of the intrusion to plagioclase- and clinopyroxene-dominated rocks in the upper portion, shows a gross consistency with a fractional crystallization process.The incompatible elements are relatively enriched in the lower portion of the intrusion which is not consistent with a broad fractional crystallization process. These variations suggest that the ultramafic portion of the KemiIntrusion is relatively enriched in trapped liquid compared to the mafic portion.Îµ2.44 Nd values ranges from +4 (consistent with depleted mantle source) to -10 (indicating a contribution from Archaean crust). The lower peridotites, pyroxenites and websterites have Îµ2.44 Nd values ranging between depleted mantle signatures and -2, whereas the gabbroic cumulates have Îµ2.44 Nd values which cover a range from around -5 to -10. Nd isotopic variation in the lower part of the profile is punctuated by distinct spikes to lower Îµ2.44 Nd corresponding to the chromitite horizons. Both the lower and upper portions of the Kemi Intrusion show enrichment of LREEC1 relative to HREEC1. The LREEC1 enriched values start to increase markedly from about the 1000 meter mark and continue to increase in value towards the roof of the intrusion.The main enrichment of PGE (Î£PPGE = 55 to 148 ppb) occurs approximately 90 to 160 m above the basal contact, beginning within andcontinuing above the main chromitite ore horizon. The mantle-normalized PGE abundances of the main chromitite horizon and the peridotites and pyroxenites below it show enrichment of IPGEPM (Os + Ir + Ru) relative to PPGEPM (Rh + Pd + Pt). In contrast, the overlying rocks are characterised by enrichment of PPGEPM relative to IPGEPM. These PGE-patterns suggest the influence of two distinct controlling processes above and below the main chromitite reef.The isotopic data are consistent with the initial introduction of multiple pulses of depleted mantle-derived magma crystallising olivine and pyroxene. Before the parent magma was fed into the Kemi magma chamber, it underwent crustal contamination and assimilation in a staging chamber within the lower crust. Some of these pulses were "critically crustally contaminated" , inducing chromite saturation and precipitation. The modelling also predicts minor in-situ contamination of the parent magma in the Kemi chamber with its wall and roof rocks. Above the main chromitite layer (about 160 m above the basal contact), the chromite content decreases and the PPGEPM/IPGEPM values increase which is consistent with scavenging of the IPGE into the lowermost layers and/or evolving magma compositions. Above 1000 m, the isotopic and REE data indicate a new magma pulse which has also been extensively contaminated in the staging magma chamber before emplacement into the Kemi magma chamber. The contamination in the staging magma chamber increased which is reflected in a progressively larger crustal component towards the top of the Kemi Intrusion
Keywords: Chromite -- Finland -- Kemi; Mining geology -- Finland -- Kemi; Geochemistry -- Finland -- Kemi; Petrology -- Finland -- Kemi